Artist and themes: a study on social commentary photographic images / Husaini Yaacob - Yaacob, Husaini (Institute of Graduate Studies, UiTM, 2015)
Social commentary is an alternative method to convey messages to the public with the hope to change their perceptions and attitudes toward certain social issues of ethical, political, moral and even religious. There have been various methods that have been used either in the form of electronic or printed medium. One of the methods has been the photographic images which have been used by the photography artists to convey their messages. This is called as the social commentary. In the advanced countries, social commentary images have long been accepted by the public and has become one of the most powerful medium of communication to alert or trigger the society toward change. In some developing countries as such in Malaysia, the acceptance of social commentary photography among the public is still arguable about the usage of photographic images as a medium of communication which has not been fully accepted and understood by the public. Most of the public has not been aware of what have been posted by the photography artists. Therefore, the photography artworks on social commentary which have been produced by these photography artists in Malaysia have just become an ordinary exhibited materials that do not carry any message or impact to the public…